Inclusive Education in Islamic Boarding Schools through Guidance and Counseling for Religiosity and Spirituality - Naqiyah, Najlatun; Faidah, Mutimmatul; Hariastuti, Retno Tri; Putri, Diajeng Retno Kinanti; Lidyawati, Reky (KONSELOR, 2024)
Inclusive Education is education that is open to all groups of people. Inclusive-based education in Islamic boarding schools (pondok pesantren) is to serve all students of different backgrounds. Students in Islamic boarding schools are composed of different backgrounds and personal identities, as students with inclusive values. Adaptation with the school environment requires self-efficacy in religiosity and spirituality. Self-efficacy can provide encouragement to students enrolled in Islamic boarding schools. Self-efficacy is a feeling of success through possessed abilities to achieve individual life goals. Self-efficacy gives a positive psychological impact towards a person in their lives. Research results indicated that there is a need for guidance and counseling services that can increase the self-efficacy of students yet allow them to stand firm in their religiosity and spirituality. To respond to this matter, there is the need for an application that students may use in any situation and condition. Therefore, the Islamic Guidance and Counseling Application (IGCA) answers the needs of education in Islamic boarding schools. The utilized method in this research was the qualitative method with observations, interviews, and documentation to examine the religiosity and spirituality of students in Islamic boarding schools. The research results are expected to be able to accommodate the needs of counselors in Islamic boarding schools with an inclusive approach for guidance and counseling of religiosity and spirituality.